Measurement of the mechanical and dynamic properties of 3D printed polylactic acid reinforced with graphene. Issue 11 (24th July 2019) - Mansour, M.; Tsongas, K.; Tzetzis, D.
ABSTRACT: In this paper, three-dimensional (3D) printing system based on fused deposition modeling (FDM) is used for the fabrication of polylactic acid (PLA) specimens with and without graphene and to measure their dynamic mechanical properties. In particular, 3D printed PLA/graphene nanocomposites containing 10wt% graphene in PLA matrix were characterized by compression tests, cyclic compression tests, nanoindentation and modal tests. The results of the mechanical tests reveal that the incorporation of multifunctional graphene has improved the modulus, the strength and the hardness of the 3D printed nanocomposites. The damping as calculated by cyclic compression and modal tests was substantially increased compared to neat PLA samples. Graphical Abstract: